1985
DOI: 10.1111/j.1600-051x.1985.tb01401.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical procedure for determining the proficiency of gingivitis examiners

Abstract: The purpose of the present study was to evaluate a clinical procedure for determining the proficiency of gingivitis examiners. After 4 examiner trainees were instructed by and participated in practice examination sessions with a senior examiner, the 5 examiners participated in a 2-group clinical study which employed appropriately timed-staggered dental prophylaxes to create a gingivitis treatment effect between the 2 groups. The 1st group received dental prophylaxes 30 days before the 2nd group. 10 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This has been shown to be highly effective in reducing gingivitis 10 . Sturzenberger 11 reported that the greatest effect of a dental prophylaxis on gingivitis can be observed 7 to 10 days after treatment, following this gingivitis increased with the recurrence of dental plaque. In healthy patients, the typical time period between dental cleanings is six months.…”
mentioning
confidence: 99%
“…This has been shown to be highly effective in reducing gingivitis 10 . Sturzenberger 11 reported that the greatest effect of a dental prophylaxis on gingivitis can be observed 7 to 10 days after treatment, following this gingivitis increased with the recurrence of dental plaque. In healthy patients, the typical time period between dental cleanings is six months.…”
mentioning
confidence: 99%
“…While conducting a study designed to train examiners in using gingival indices Sturzenberger et al 10 . reported that within 7–10 days after a dental prophylaxis one can see the greatest decrease in gingival inflammation.…”
Section: Maintenance Of Gingival Healthmentioning
confidence: 99%
“…While conducting a study designed to train examiners in using gingival indices Sturzenberger et al 10 reported that within 7-10 days after a dental prophylaxis one can see the greatest decrease in gingival inflammation. Clinical gingival health is identified by minimal sulcus depth, stippling, gingival colour of pale or coral pink with a knife edge that adapts closely around the tooth with no evidence of bleeding when probed.…”
Section: Maintenance Of Gingival Healthmentioning
confidence: 99%
“…The purpose of this presentation is to present a methodology for assessing the reliability of such an index, be it a plaque, gingival inflammation, or periodontal index. The PMGI (De la Rosa & Sturzenberger 1976) will be used to illustrate the methods, using data from a study in which gingivitis was assessed with a non-invasive form of this index (Sturzenberger et al 1985). A schematic of the study design is given in Fig.…”
mentioning
confidence: 99%